Changes in the specific absorption rate (SAR) of radiofrequency energy in patients with retained cardiac leads during MRI at 1.5T and 3T. Issue 1 (12th June 2018) - Golestanirad, Laleh; Rahsepar, Amir Ali; Kirsch, John E; Suwa, Kenichiro; Collins, Jeremy C.; Angelone, Leonardo M.; Keil, Boris; Passman, Rod S.; Bonmassar, Giorgio; Serano, Peter; Krenz, Peter; DeLap, Jim; et al.
Abstract : Purpose: To evaluate the local specific absorption rate (SAR) and heating around retained cardiac leads during MRI at 64 MHz (1.5T) and 127 MHz (3T) as a function of RF coil type and imaging landmark. Methods: Numerical models of retained cardiac leads were built from CT and X‐ray images of 6 patients with retained cardiac leads. Electromagnetic simulations and bio‐heat modeling were performed with MRI RF body and head coils tuned to 64 MHz and 127 MHz and positioned at 9 different imaging landmarks covering an area from the head to the lower limbs. Results: For all patients and at both 1.5T and 3T, local transmit head coils produced negligible temperature rise ( Δ T < 0.1 ° C ) for ‖ ‖ B 1 + ‖ ‖ ≤ 3 μ T . For body imaging with quadrature‐driven coils at 1.5T, Δ T during a 10‐min scan remained < 3°C at all imaging landmarks for ‖ ‖ B 1 + ‖ ‖ ≤ 3 μ T and <6°C for ‖ ‖ B 1 + ‖ ‖ ≤ 4 μ T . For body imaging at 3T, Δ T during a 10‐min scan remained < 6°C at all imaging landmarks for ‖ ‖ B 1 + ‖ ‖ ≤ 2 μ T . For shorter pulse sequences up to 2 min, Δ T remained < 6°C for ‖ ‖ B 1 + ‖ ‖ ≤ 3 μ T . Conclusion: For the models based on 6 patients studied, simulations suggest that MRI could be performed safely using a local head coil at both 1.5T and 3T, and with a body coil at 1.5T with pulses that produced ‖ ‖ B 1 + ‖ ‖ ≤ 4 μ T . MRI at 3T could be performed safely in these patients using pulses with ‖ ‖ B 1 + ‖ ‖ ≤ 2 μ T .